1999
DOI: 10.1063/1.370331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cluster/particle deposition on atmospheric pressure chemical vapor deposition of SiO2 from four gaseous organic Si-containing precursors and ozone

Abstract: In order to analyze the particle generation and its effect on the SiO 2 thin film in an atmospheric pressure chemical vapor deposition ͑APCVD͒ process using four organic silicon vapors and ozone gas, gas-phase particle generation, growth, transportation and vapor-cluster/particle codeposition processes were studied experimentally and theoretically using a flow-type vertical tube reactor. Decomposition reaction rates of four organic silicon vapors ͑tetraethylorthosilicate, triethoxysilane, tetramethylorthosilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Vapour phase manipulation of silica and its controlled deposition is already a well-established technology 2 with the production of vapours of SiO 2 -based species quite routinely performed through the use of siliconcontaining molecular intermediates and highly oxidative conditions. Vapour phase oxidation of silane (SiH 4 ) 3,4 and TEOS (tetraethyl-orthosilicate) 5 molecules, for example, have been successfully employed to produce sources of molecular SiO 2 which can be used to produce very pure silica films and coatings. Although intrinsically relying on the nucleation of pure SiO 2 species, these methods further involve numerous other complex reaction/decomposition routes involving organosilica components.…”
Section: Introductionmentioning
confidence: 99%
“…Vapour phase manipulation of silica and its controlled deposition is already a well-established technology 2 with the production of vapours of SiO 2 -based species quite routinely performed through the use of siliconcontaining molecular intermediates and highly oxidative conditions. Vapour phase oxidation of silane (SiH 4 ) 3,4 and TEOS (tetraethyl-orthosilicate) 5 molecules, for example, have been successfully employed to produce sources of molecular SiO 2 which can be used to produce very pure silica films and coatings. Although intrinsically relying on the nucleation of pure SiO 2 species, these methods further involve numerous other complex reaction/decomposition routes involving organosilica components.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of plasma-enhanced reactions in the gas-phase have been studied for simple or commonly used chemicals, such as silane (SiH 4 ) and tetraethylorthosilicate (TEOS), (24)(25)(26)(27)(28)(29)(30) for the deposition of silicon dioxide. A few experimental studies exist for the deposition of silicon dioxide using other organic silicon compounds, including hexamethyldisiloxane (HMDSO, Si 2 O(CH 3 ) 6 ) (25,29,(31)(32)(33) and OMCTS, (26,28,30,34,35) and oxygen or ozone. Although the detailed plasma reaction kinetics for HMDSO and OMCTS remains unknown, it has been found that reaction between O 3 and silicone vapor molecules are negligible and the dominant reactions to form precursors for the deposition are those between O and the organiosilicone molecules.…”
Section: Gas-phase Chemical Mechanismsmentioning
confidence: 99%
“…Fujimoto et al (28) estimated the rate coefficient by assuming Si 8 O 9 (CH 3 ) 14 is the dominant silicon-containing product from the global reaction. They obtained the rate coefficient by matching the numerically predicted particle number concentration using a discrete-sectional model (53) with the measured particle number concentration in the gas phase.…”
Section: Gas-phase Chemical Mechanismsmentioning
confidence: 99%